Laju Metabolisme dan Saturasi Oksigen Kelelawar Pemakan Buah (Cynopterus titthaecheilus) - Rahma, Anisa; Hanadhita, Desrayni; Maheshwari2, Hera; Sismin Satyaningtijas, Aryani; Agungpriyono, Srihadi (IPB University, 2025)
Metabolic rate and oxygen saturation are crucial factors in understanding the physiology of fruit bats (Cynopterus titthaecheilus and Cynopterus brachyotis). This study aims to evaluate the resting metabolic rate and oxygen saturation in bats and their relationship to flight physiology. A total of 32 bats were categorized based on species, sex, and age. Metabolic rate was measured using a metabolic chamber method, while oxygen saturation was monitored using a patient monitoring system. The results showed that bat metabolism is influenced by various factors, including age and sex, without a significant correlation with body mass. Adult female bats exhibited highly fluctuating metabolic rates, possibly due to hormonal factors and increased energy demands during lactation. Additionally, C. titthaecheilus had an oxygen saturation of 94%±2.00 for males and 94%±1.73 for females, whereas C. brachyotis showed 98%±0.00 in males and 87%±4.16 in females. The high oxygen saturation in bats indicates an efficient oxygen transport system that supports their high metabolic activity during flight. This study provides insights into the physiological strategies of bats in maintaining high metabolism and oxygenation capacity, which are relevant to their ecology and overall health.